Kauśāmbī hoard of Magha coins : a study of the Magha coinage based on the Kauśāmbī hoard - Shastri, Ajay Mitra (Nagpur University, 1979)
Detailed analysis of the coins issued by Magha rulers of Uttar Pradesh.